2018
DOI: 10.1111/and.12978
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid improves the quality of boar semen subjected to cooled storage at 15°C

Abstract: The aim of this study was to investigate the effect of chlorogenic acid (ChA) in boar semen stored at 15°C. Twelve ejaculates were processed into insemination doses at different concentrations of ChA (0.0, 1.5, 3.0, 4.0 and 6.0 mg/ml) or vitamin E (200 μl/ml) as positive control. Semen was analysed after 0, 24 and 72 hr of storage. ChA improved (p < .05) sperm motility, acrosome integrity and mitochondrial activity in all periods of storage. Furthermore, after 24 hr of storage, ChA above 1.5 mg/ml supported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Thus, alternatives that can prolong sperm resistance time after re-warming are important. Pereira et al (2018), evaluating different doses of ChA (0.0, 1.5, 3.0, 4.0 and 6.0mg/ml) concluded that the concentration of 3.2mg/ml of this substance is the best for semen stored for 24h. However, for semen stored for a longer period, 6.0mg/ml or more should be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, alternatives that can prolong sperm resistance time after re-warming are important. Pereira et al (2018), evaluating different doses of ChA (0.0, 1.5, 3.0, 4.0 and 6.0mg/ml) concluded that the concentration of 3.2mg/ml of this substance is the best for semen stored for 24h. However, for semen stored for a longer period, 6.0mg/ml or more should be used.…”
Section: Discussionmentioning
confidence: 99%
“…This solution was then added to the volume of semen that contained 1.5 billion sperm. After, BTS at 37°C were then added until the final volume of 40ml, so that each insemination dose contained 4.5mg of ChA per ml of semen (Pereira et al, 2018). Two inseminate doses were processed with ChA and two without this substance.…”
Section: Allmentioning
confidence: 99%
See 1 more Smart Citation
“…It displays different pharmacological activities such as antioxidant, anti-inflammatory, anti-microbial, hepatoprotective, anticancer, anti-lipidemic, and anti-diabetic [ 29 ]. A concentration of 100 µM CGA yielded beneficial effects on sperm motility, viability, and plasma membrane integrity in boar semen during freezing [ 30 ] and cooling at 15 °C [ 31 , 32 ]. CGA also displayed a positive effect in in vitro production of porcine embryos and a protection against DNA damage induced by OS in oocytes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we summarize recent literature on the effects of CGAs on different features of health (Table 1 (Tab. 1) ; References in Table 1: Bao et al, 2018[ 2 ]; Chen et al, 2017[ 3 ]; Chen et al, 2018[ 4 ]; Cheng et al, 2019[ 5 ]; Ding et al, 2017[ 7 ]; Gao et al, 2018[ 4 ]; Guo and Li, 2017[ 9 ]; Huang et al, 2017[ 10 ]; Kaneda et al, 2018[ 11 ]; Kato et al, 2018[ 12 ]; Kim et al, 2018[ 13 ]; Lee and Lee, 2018[ 14 ]; Li et al, 2018[ 15 ]; Liu et al, 2017[ 16 ]; Lou et al, 2016[ 17 ]; Ma et al, 2018[ 18 ]; Martínez et al, 2017[ 20 ]; Mei et al, 2018[ 21 ]; Miao et al, 2017[ 22 ]; Moghadam et al, 2017[ 23 ]; Nguyen et al, 2017[ 25 ]; Park et al, 2017[ 26 ]; Pereira et al, 2018[ 27 ]; Refolo et al, 2018[ 28 ]; Sanchez et al, 2017[ 29 ]; Siebert et al, 2018[ 31 ]; Song et al, 2018[ 32 ]; Tan et al, 2016[ 34 ]; Vukelić et al, 2018[ 37 ]; Wang et al, 2016[ 38 ]; Wei et al, 2018[ 39 ]; Xue et al, 2017[ 40 ]; Yamagata et al, 2018[ 41 ]; Yan et al, 2017[ 42 ]; Yan et al, 2018[ 43 ]; Yang et al, 2017[ 44 ]; Ye et al, 2016[ 45 ]; Yuan et al, 2017[ 46 ]; Yun and Lee, 2017[ 47 ]; Zhang et al, 2017[ 48 ]; Zhou et al, 2016[ 50 ]; Zhu et al, 2018[ 51 ]).…”
mentioning
confidence: 99%